Richard Hooker and reformed theology a study of reason, will, and grace - Voak, Nigel; Oxford eBooks (Oxford : Oxford University Press, 2003)
Richard Hooker (1554-1600) is one of the greatest theologians of the Church of England. In the light of fierce recent debate this book argues against the new orthodoxy that Hooker was a Reformed or Calvinist theologian. It considers such central religious questions as human freedom and original sin.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hooker, Richard, -- 1553 or 4-1600.; Theology, Doctrinal; Reason; Will -- Religious aspects -- Christianity; Grace (Theology); Electronic books